Impact of neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR), systemic inflammation index (SII), systemic inflammation response index (SIR-I), and aspartate transaminase/platelet ratio (APRI) in predicting pregnancy outcom (Annals of Medical Research, 2023)
Aim: We aimed to investigate the effect of systemic inflammation indices in predicting pregnancy outcomes of inflammatory bowel disease (IBD).Materials and Methods: Pregnant women with  Crohn’s disease (CD) and Ulcerative colitis (UC) were identified from hospital medical records. Demographic features, disease type, duration and activity, and obstetric outcomes such as gestational age,  mode of delivery, birth weight, Apgar scores at the first and fifth minutes after birth, and neonatal intensive care unit admission were assessed. Laboratory tests were conducted in the first trimester, including complete blood count and liver function. Neutrophil/lymphocyte ratio (NLR), derived neutrophil/lymphocyte ratio (dNLR), systemic inflammation index (SII), systemic inflammation response index (SIR-I), and aspartate transaminase/platelet ratio (APRI) were measured.Results: The study involved 48 pregnant women, 26 diagnosed with UC and 22 with CD. At least one attack occurred in 31.3% of all patients during pregnancy. For predicting attacks during pregnancy, the optimal cutoff values of dNLR, NLR, SII, SIR-I, and APRI were 2.12 (86.7% sensitivity, 82.8% specificity), 2.89 (86.7% sensitivity, 81.8% specificity), 850.7 109/L (66.7% sensitivity, 63.6% specificity), 1.06 109/L (66.7% sensitivity, 72.7% specificity), 0.051 (80% sensitivity, 75.8% specificity), respectively. A cut-off value of 0.07 for APRI ( 71.4% sensitivity and 73.2% specificity) was calculated to predict low birth weight.Conclusion: NLR, dNLR, SII, SIR-I, and APRI might help predict attacks in pregnant women with IBD. In addition, APRI may be utilized to predict low birth weight in pregnant women with IBD.
Keywords: Inflammatory bowel disease; Pregnancy; Systemic inflammation index